Configurations of mathematical objects and mathematical processes of integral calculus - Suárez, Leidy Johana; Suárez, Nury Yolanda (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Results of a research are presented, in which mathematical classes were analyzed following the onto-semiotic approach. The research approach was qualitative with an ethnographic method of case study. A didactic analysis of a class of integral calculus divided into four moments was carried out, in which the mathematical objects and processes were identified. It was determined what types of semiotic conflicts are generated. It is highlighted that the processes on the part of the professor are those of institutionalization, representation, materialization, idealization and reification. Sometimes there are processes of signification and generalization. On the part of the students, the most common processes are those of representation, materialization and idealization. Processes of personalization and reification rarely occur, since the way in which the teacher gives the class does not allow identifying when each student participates in the construction of meanings.